Strategi Pemerintah Daerah Dalam Sosialisasi Kebijakan Pandemi Covid-19 Di Tangerang Selatan - Andrean Utama Putra; Lubna Salsabila; Sahat Sianturi (Prodi Ilmu Administrasi Negara, 2022)
The goal of this research is to look into the role of local governments in lobbying for and carrying out any federal policy or program. Concerning the flow of communication from the government to the community, the research that was undertaken explored in great detail the communication that occurred between regional government workers. The descriptive method with a qualitative approach was employed as the research methodology in this study. Furthermore, Edward III's theory was used to investigate the stages of communication and their role in socializing the policy of the Government of South Tangerang City. This data was gathered through interviews, observations, and written documentation. The study's findings revealed that policy socialization is progressing very well through various communication channels such as internet media, printed media, and electronic media. The study also demonstrated that this socialization is going quite nicely. These numerous sorts of socialization media were the principal tools used by the South Tangerang regional government to socialize its varied policies. Another way to socialize was to distribute direct media or socialization to each neighborhood. It is advised that the South Tangerang City Government continue to work to improve their performance in socializing policies so that they will achieve the goals of the policies established in order to build a society that is lawful and orderly in relation to the policies that were made.